Experimental investigation on coal-breakage performances by abrasive nitrogen-gas jet with a conical nozzle. (June 2021) - Hong, Chunyang; Yang, Ruiyue; Huang, Zhongwei; Liu, Wei; Chen, Jianxiang; Cong, Richao
Abstract: With the increasing energy and environmental protection demands, coalbed methane (CBM) have attracted worldwide attentions. A cost-effective way of using nitrogen-gas as the fluid media of abrasive jet for radial jet drilling (RJD) in CBM exploitation was proposed in this paper. Laboratory experiments were carried out to investigate the influence of parameters including jetting pressure, nozzle diameter, dimensionless standoff distance, bedding direction, abrasive diameter, duration time and coal strength on coal-breakage efficiency. Besides, sensitivity analysis was conducted to evaluate the effect of jetting parameters on erosion performance. Moreover, the surface morphologies of jet-drilled holes were measured by a 3D profilometer. Finally, the coal-breakage mechanisms of abrasive nitrogen-gas jet were illustrated. The results indicated that the key factors for improving coal-breakage efficiency by abrasive nitrogen-gas jet were dimensionless standoff distance and nozzle diameter. Four major factors that contribute to the coal-breakage mechanisms can be summarized as: fractures generation, edge chipping, repeated erosion and gas entrainment effect. Moreover, jetting direction plays an important role in generating fractures. Fractures tend to be generated along the parallel bedding direction on the coal since tensile failures are easier to be occurred. Furthermore, a regular and smooth hole generated by the abrasive nitrogen-gas jet made it suitable for RJD drilling in CBM wells. The experimental results are expected to provide a viable alternative for efficient, economical and safe exploitations in CBM reservoirs.